Morphometric and Hydrological Analysis of Migdal Valley Basin: Morphometric and Hydrological Analysis of Migdal Valley Basin (Journal of Humanitarian and Applied Sciences, 2026)
This research aims to analyze the morphometric and hydrological characteristics of the Migdal Valley basin using Geographic Information Systems (GIS) and Digital Elevation Models (DEMs) to understand its hydrological behavior and evaluate flood hazards. The study identified that the basin covers an area of 83.72 km², with a length of 20.36 km and an average width of 4.11 km, indicating an elongated basin shape. Elevation ranges from 30 m to 360 m, with a relief of 330 m, reflecting considerable topographic variation that influences runoff and flow velocity. The drainage network analysis revealed 91 channels with a total length of 504 km and a drainage density of 3.117 km/km². Hydrological parameters showed a lag time of 3.32 minutes and a concentration time of 2.12 hours, indicating a rapid response to rainfall events. The basin demonstrates high flash-flood susceptibility and considerable potential for water harvesting and sustainable
Keywords: Morphometric analysis; Wadi Migdal Basin; Drainage network; Drainage density; Geographic Information Systems (GIS)